The Community Pediatrics Training Initiative Project Planning Tool: A Practical Approach to Community-Based Advocacy - Benjamin D. Hoffman; Jerri Rose; Debra Best; Julie Linton; Steven Chapman; Michele Lossius; Andrew Aligne; Cappy Collins; Lisa Ayoub-Rodriguez (Association of American Medical Colleges, 2017)
Introduction To impact social determinants of health, physicians require knowledge, skills, and attitudes to work with communities beyond the clinical milieu. The American Academy of Pediatrics (AAP) Community Pediatrics Training Initiative (CPTI) project planning tool can guide health care professionals and trainees to identify and define issues, build coalitions, assess interventions, and ensure sustainability of successful programs. The Accreditation Council for Graduate Medical Education guidelines for pediatric training require experiences in community health. To date, there have been no widely available tools to ensure both robust learning and validated assessment for pediatric residents in community pediatrics and advocacy training. Methods The AAP CPTI project planning tool engages learners with a step-by-step process involving investigation, guided reflection, and structured assessment. Learners practice the skills necessary to plan, implement, and evaluate a community pediatrics/child health advocacy proposal focused upon a learner-defined area of interest. An assessment rubric maps to milestones. Results This project planning tool has been used in a number of programs with learners at multiple levels, including undergraduate education, graduate education, and practicing health care providers. It can be employed to design and implement a community advocacy intervention or as a thought exercise and can be incorporated in a single block rotation or as a longitudinal experience. It can be used with individual learners or as a group exercise. Discussion The project planning tool can be used by residency programs to demonstrate resident competence in community health and advocacy, either as a learning exercise or to guide actual implemented projects.